2011
DOI: 10.1097/ta.0b013e31822c8865
|View full text |Cite
|
Sign up to set email alerts
|

Early Parenchymal Contrast Extravasation Predicts Subsequent Hemorrhage Progression, Clinical Deterioration, and Need for Surgery in Patients With Traumatic Cerebral Contusion

Abstract: Early parenchymal CE is associated with hemorrhage progression, cerebral edema, clinical deterioration, and need for subsequent surgery. These patients should be monitored closely, and early surgery may be needed if deterioration occurs. Further elucidation of the pathophysiology is needed to formulate effective treatment for these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 20 publications
2
29
2
3
Order By: Relevance
“…A potential major caveat of our finding is the difference in CTA/PCCT acquisition protocols across different centers, which can potentially mitigate the external validity of these results and mandate reproduction in other centers. For example, Huang et al 25 did not identify any CTA-positive extravasation foci; all the observed extravasation foci were identified on the PCCT, and, contrary to our results regarding PCL, PCCT extravasation foci were significantly associated with hemorrhage progression (by using a different threshold of Ͼ5 mL or 30%), clinical deterioration, and the need for surgery. We encountered a slightly higher rate of extravasation per patient (50%) compared with 43% in the study by Huang et al 25 This difference is likely related to the inclusion of extra-axial hematomas in our study, especially epidural hematomas, which showed higher prevalence of extravasation.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…A potential major caveat of our finding is the difference in CTA/PCCT acquisition protocols across different centers, which can potentially mitigate the external validity of these results and mandate reproduction in other centers. For example, Huang et al 25 did not identify any CTA-positive extravasation foci; all the observed extravasation foci were identified on the PCCT, and, contrary to our results regarding PCL, PCCT extravasation foci were significantly associated with hemorrhage progression (by using a different threshold of Ͼ5 mL or 30%), clinical deterioration, and the need for surgery. We encountered a slightly higher rate of extravasation per patient (50%) compared with 43% in the study by Huang et al 25 This difference is likely related to the inclusion of extra-axial hematomas in our study, especially epidural hematomas, which showed higher prevalence of extravasation.…”
Section: Discussioncontrasting
confidence: 56%
“…Akin to prior nontraumatic ICH studies [12][13][14][15][16][17][18][20][21][22]38 and a smaller cerebral contusion study, 25 our results demonstrate the prognostic value of contrast extravasation in traumatic intracrananial injuries. Similarly, earlier MR imaging series evaluated "enhancement" of traumatic intra-and extra-axial hematomas, also suggesting a predictive value of extravasation in this setting but were limited by significantly smaller sample sizes.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations